The mediating role of surface and deep acting and the moderating effect of occupational identity in workplace violence and sleep quality among psychiatric nurses: a cross-sectional study - Ke Zhang; Jiayi Wang; Yuekun Wu; Di Zhang; Chenxin Yang; Hui Wu (BMC, 2024)
Abstract Background Psychiatric nurses often encounter patients with mental health disorders and consequently experience prolonged periods of high stress, increased workload, and frequent incidents of workplace violence. These aspects can lead to a higher incidence of poor sleep quality. This study examined the interplay between workplace violence and emotional labour (surface and deep acting) to suggest measures for enhancing sleep quality among psychiatric nurses. Methods A total of 300 completed and valid online questionnaires were collected. The Pittsburgh Sleep Quality Index was used to measure sleep quality, Workplace Violence Scale (WVS) to measure the occurrence of workplace violence, and Emotional Labour Scale to measure surface and deep acting. The data were analysed using Hayes' PROCESS macro with SPSS. Independent samples t-tests and one-way ANOVA were used to compare differences in sleep quality and emotional labour (surface and deep acting) between psychiatric nurses with different demographics. Results The prevalence of poor sleep quality (PSQI > 5) was 55% among the nurses. Surface acting in emotional labour partially mediated the relationship between workplace violence and sleep quality(a1*b1=0.035,95%CI: 0.002, 0.079), whereas deep acting had a suppressive effect(a2*b2=-0.033,95%CI: -0.071, -0.003). Occupational identity had a positive moderating effect on the relationship between workplace violence and surface acting(Effect=0.091,95%CI: 0.004, 0.179). Conclusions The relationship between workplace violence and poor sleep quality was partially mediated by surface acting and suppressed by deep acting. Moreover, nurses with higher occupational identity engaged in more surface acting after workplace violence. Workplace violence, surface acting, and deep acting emerged as significant factors influencing sleep quality among psychiatric nurses. Deep acting can reduce the impact of workplace violence on sleep quality. The results provide a new and expanded view of the interplay between workplace violence and emotional labour concerning sleep quality. Interprofessional collaboration with clinicians, administrators, educators, and spiritual leaders can contribute to the development of related education and training. Trial registration Chinese Clinical Trial Registry ChiCTR2200062347. https://www.chictr.org.cn/showproj.html?proj=173264